Gallstone Illeus, a difficult diagnosis: Case Report - Saenz, Luis; Portillo, Elizabeth Mendoza; Bravo, Alejandro Badillo; Vallejo, Fausto Romero; González, Oswaldo Díaz; Rossano, Michelle Mendoza; Portillo, Eduardo Muñoz; Moyron, Miguel Fernando Juárez; Galicia, Azalia Rosalia Pérez; Ocampo Vargas, Alan Karecci; et al. (British Journal of Healthcare and Medical Research, 2020)
Gallstone ileus is a rare cause of mechanical bowel obstruction seen in patients with a history of cholelithiasis or cholecystitis. Its diagnosis is difficult since it presents vague and nonspecific symptoms. This is the case of a 69-year-old woman with a history of arterial hypertension and type 2 diabetes mellitus, without a surgical history, who is admitted to the emergency room due to abdominal pain. Her diagnosis is based on contrast X-ray images, computed tomography (CT) and upper gastrointestinal endoscopy. Surgery remains being the gold standard treatment.